The gene structure of human anti-haemophilic factor IX. - Anson, D S (1984)
The mRNA sequence of the human intrinsic clotting factor IX (Christmas factor) has been completed and is 2802 residues long, including a 29 residue long 5' non-coding and a 1390 residue long 3' non-coding region, but excluding the poly(A) tail. The factor IX gene is approximately 34 kb long and we define, by the sequencing of 5280 residues, the presumed promoter region, all eight exons, and some intron and flanking sequence. Introns account for 92% of the gene length and the longest is estimated to be 10 100 residues. Exons conform roughly to previously designated protein regions, but the catalytic region of the protein is coded by two separate exons. This differs from the arrangement in the other characterized serine protease genes which are further subdivided in this region.